Wild boar (Sus scrofa) carcasses as an attraction for scavengers and a potential source for soil contamination with the African swine fever virus - Tummeleht, Lea; Häkkä, Susanna Suvi Siviä; Jürison, Margret; Vilem, Annika; Nurmoja, Imbi; Viltrop, Arvo (Frontiers in Veterinary Science, 2024)
The wild boar (Sus scrofa) is a social animal species native to Eurasia. During the last decade, the wild boar population in Estonia has been severely affected by the African swine fever virus (ASFV), which has also affected domestic pig farming. The potential transmission routes of ASFV remain unclear and are currently under intensive investigation. This pilot study aimed to clarify the frequency and characteristics of contacts between living wild boars and the carcasses of their conspecifics, which could play a role in the transmission of ASFV. Wild animals' contact and scavenging behavior on wild boar carcasses were studied using trail cameras in an experimental setting on Hiiumaa Island, Western Estonia. Four legally hunted carcasses were used in the present study. This study aimed to determine whether intraspecies scavenging occurs in wild boars. The persistence of ASFV DNA in soil contaminated with infected wild boar carcasses was investigated separately. Among 17 identified wildlife species visiting wild boar carcasses, the common raven (Corvus corax) was the most frequent (37.26%), followed by raccoon dogs (Nyctereutes procyonoides) (4.25%), carcass conspecific/wild boars (3.16%), and red foxes (Vulpes vulpes) (2.14%). Regarding the direct contact with the carcass, the same species ranking was detected: common raven (74.95%), raccoon dogs (9.94%), wild boars (4.21%), and red foxes (4.21%). No clear signs of cannibalism were noted among the wild boars, although brief physical contact with the carcasses was evident. The persistence of ASFV DNA in soil contaminated by infected wild boar carcasses was investigated separately. This study revealed that ASFV DNA from infected carcasses could be detected in forest soil for prolonged periods, even after removing the carcasses. Hence, the carcasses of infected wild boars may play an important role in spreading the African swine fever virus in wild boar populations; thus, prompt removal and disinfection of the soil could be considered necessary to limit the spread of the infection.